Pengaruh Workplace Spirituality Terhadap Kinerja Organisasi: Systematic Literature Review - Anung Pramudyo; Edi Cahyono; Dwi Wahyu Pril Ranto; Sarjita Sarjita; Nunuk Dwi Garwanti Endang Palupi; Habib Ismail (Lembaga Pengembangan Kinerja Dosen, 2026)
Using a methodical literature review technique, this study seeks to compile the most recent data about the impact of workplace spirituality on organizational performance. Using the keywords